Morfofisiologia da cunhã cultivada sob estresse salino - Martins, Silvana Souza (2012)
The experiment was developed based on the importance of the nutritional factor cunhã for large and small, animals and on the growth of this forage in typical soils of the semiarid region, generally with salinity from natural or anthropogenic action. The experiment was performed in vessels with a capacity of 5kg prepared in a protected environment with full sunshine in the Department of Technology and Social Sciences (DTCS) of UNEB Campus III in Juazeiro BA. It evaluated the effect of seven different salt concentrations on increasing levels of irrigation water electrical conductivity ECw (0, 2, 4, 6, 8, 10 and 12 dS/m), at room temperature. The analysis of culture were taken every seven days observing the number of leaves, stem diameter, plant, plant length and total chlorophyll content at 13; 20; 27; 34 and 40 days after the start of irrigation with saline . The contents of proline, the ratio aero part/Root (AP/Rt), the root length and water content were evaluated in the 40 th day after the onset of treatment. The results showed that the elevation of ECw affected all variables.